2017
DOI: 10.1016/j.fct.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin induced liver inflammation in mice by altering the gut microbiota and its metabolic functions

Abstract: Maintaining the balance of the gut microbiota and its metabolic functions is vital for human health, however, this balance can be disrupted by various external factors including food additives. A range of food and beverages are sweetened by saccharin, which is generally considered to be safe despite controversial debates. However, recent studies indicated that saccharin perturbed the gut microbiota. Inflammation is frequently associated with disruptions of the gut microbiota. The aim of this study is to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 63 publications
4
123
0
3
Order By: Relevance
“…Despite the limitations, this is the first study to provide insight into the effect of saccharin-based sweeteners such as Sucram ® on rumen microbial communities present within the content as well as on the rumen epithelium. Until now, the research conducted to identify the effects of artificial sweeteners on mammalian gastrointestinal tract microbial communities has been exclusively focused on monogastric animal models such a rats and pigs [4, 7, 40]. For example, a recent study provided evidence that certain bacteria degrade saccharin-based artificial sweeteners, indicating artificial sweeteners may not be non-caloric to the host if they are degraded to usable metabolic products [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limitations, this is the first study to provide insight into the effect of saccharin-based sweeteners such as Sucram ® on rumen microbial communities present within the content as well as on the rumen epithelium. Until now, the research conducted to identify the effects of artificial sweeteners on mammalian gastrointestinal tract microbial communities has been exclusively focused on monogastric animal models such a rats and pigs [4, 7, 40]. For example, a recent study provided evidence that certain bacteria degrade saccharin-based artificial sweeteners, indicating artificial sweeteners may not be non-caloric to the host if they are degraded to usable metabolic products [39].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kelly et al provided evidence that the addition of Sucram ® to the diet led to changes in the diversity of mucosal bacteria within the small intestine in swine, specifically a decrease in Campylobacter coli and an increase in members of the Helicobacteraceae family [3]. Additionally, a reduction of Ruminococcus was documented in a study analyzing the effect of saccharin on inflammatory molecules and gut dysbiosis in mice [40]. Although no significant differences were found for OTUs classified as Lactobacillus, Veillonellaceae , Campylobacter or Helicobacteraceae, the study reported in this manuscript observed a significant decrease in Rumincoccaceae (OTU 106) similar to other recent studies in monogastric animals [40, 42].…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 is an effective activator of hepatic signal transducers and activators of transcription 3 (STAT3) pathway and is diffusely featured as a participator in different facets of liver pathophysiology. TNF‐α as a proinflammatory cytokine can stimulate NFκB pathways and cause damage to cells (Bian et al, ). Treatment with JLus66 increased the abundance of Gram‐positive flora (Firmicutes) and decreased Gram‐negative flora (Bacteroidetes, Proteobacteria, and Fusobacteria), recovering the Gram‐positive‐to‐Gram‐negative ratio, which result in decrease in LPS, accompanied with decrease in TNF‐α and IL‐6 activities in serum, and then lightened inflammation in hepatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We also analyzed gut microbiota at the more detailed genus level by searching for genera that increased or decreased by more than four times in the HFD group compared with the CO group. Of the six genera that showed an increase in the HFD group, four were suppressed to some extent by Natto: Escherichia , which causes urinary tract infection and dysentery, Coprococcus , which digests carbohydrates and dietary fiber, Sporosarcina , which causes diseases such as inflammatory hepatitis, and Parabacteroides , which causes obesity and type 2 diabetes . Ruminococcus , which degrades dietary fiber such as cellulose and improves the condition of the intestinal environment, was increased more than fourfold in the HFD group and further increased by Natto intake.…”
Section: Discussionmentioning
confidence: 99%